A SST-constructed Ocean Heat Content index in crossing ENSO spring persistence barrier - Meng, Xing; Chen, Hui; Zhang, Li; Jin, Yishuai; Wu, Lixin (Frontiers in Marine Science, 2023)
The El Niño-Southern Oscillation (ENSO) spring persistence barrier (SPB) describes the feature in which the predictive skills of ENSO decrease significantly in the boreal spring. This paper investigates an index constructed using sea surface temperature (SST), namely SSTH, which is based on tropical Pacific Ocean Heat Content (OHC) in crossing ENSO SPB. Inspired by the dynamical relationship between the tropical Pacific OHC and eastern Pacific SST anomalies, SSTH is constructed by SST anomalies (i.e., Niño3.4 index) to represent OHC. We show that this index leads ENSO SST anomalies by about 10 months, making it effective in crossing ENSO SPB. Particularly, among the 50 ENSO events from 1950 to 2022, 27 years were identified to be caused by SSTH signals. Compared with warm water volume (WWV) or the west of WWV (WWVw), this index is more stable and effective after the 21st century because the effective region of subsurface OHC changed dramatically afterward. However, SSTH avoids this problem as it is constructed by SST anomalies alone. Finally, as SST data is reliable before 1980, SSTH is utilized to study the interdecadal lead-lag relationship between subsurface OHC and ENSO SST.